Dressed up problems - the danger of picking the inappropriate dress - Muzsnay, Anna; Szabó, Csaba (Teaching Mathematics and Computer Science, 2017)
Modelling and dressed-up problems play an inevitably unavoidable role in mathematics education. In this study we would like to point out how dangerous is it to dress up mathematical problems. We go back to the principle of De Lange: The problem designer is not only dressing up the problem, but he is the solution designer, as well. We show three examples selected from Hungarian high school textbooks where the intended solution does not solve the problem, because the dressing changes the context and changes the problem itself.